3D modelling of non-uniform and turbulent flow in vertical slot fishways. (January 2018) - Fuentes-Pérez, J.F.; Silva, A.T.; Tuhtan, J.A.; García-Vega, A.; Carbonell-Baeza, R.; Musall, M.; Kruusmaa, M.
Abstract: Global stocks of freshwater fish have been on the decline for decades, driven in part by the obstruction of their migration routes by anthropogenic barriers. To mitigate such impacts, fishways have been developed to facilitate bidirectional fish migration. These structures are affected by the hydrological variability of rivers, which can cause changes in the up and downstream boundary conditions of fishways, leading to non-uniform hydraulic performance. Current methodologies in fishway design and analysis often assume uniform performance, most commonly relying on 1D approximations of the water level distribution. In this study we highlight the necessity of considering non-uniform performance. We provide an in-depth analysis methodology for non-uniform conditions, demonstrating the necessity of 3D models to correctly characterize non-uniformity and leveraging the synergy between 1D and 3D models. For this VOF method together with two turbulence modelling technics, RANS Standard k-ε and LES Smagorinsky models, are analyzed using OpenFOAM CFD platform. Highlights: Non-uniform performance of vertical slot fishways is modelled in 3D domain. Two turbulence modelling techniques: RANS Standard k-ε and LES Smagorinsky models. Representative variables are compared for the two CFD results and experimental data. LES Smagorinsky models outstands when modelling turbulence variables. Results are compared to previous non-uniform modelling methods, showing their possible synergy.